Las malas prácticas bancarias no rectificadas: Una medición de su influencia en la desconfianza de la clientela - Carmen Lozano Gutiérrez; Federico Fuentes Martín (Atlantic Review of Economics, 2015)
– Present article is contextualized in an evolved market as the banking where there is a high level of competition that leads in many cases to the marketing of wide range of financial products based on limited information or untransparent, presence of surprise or unfair terms or other type of proceedings qualified as bad banking or unethical practices. The response from the Bank of Spain (supervisor) in favor of the claimants and against the actions of the financial institution is not binding so that entities may choose not to rectify its performance. An application of the fuzzy incidence matrix is carried out in order to detect and analyse a possible indirect correlations between the rate of complaints in customer's behalf not rectified by the entity and the levels of mistrust and sense of impunity that the bank client perceives from the Bank of Spain and financial institutions.
Keywords: C63; G29; E58; 330; Bank; Ethic; Fuzzy Logic; Fuzzy Incidence Matrix